LEGAL TREATMENT OF GRANT-BACK CLAUSES IN LICENCE AGREEMENTS FROM THE ASPECT OF EU COMPETITION LAW - Aleksandra (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
In this paper, the author explores the legal treatment of no challenge clauses in license agreements. A grant-back clause obligates the licensee to grant the rights on future advances or improvements in the licensed technology to the licensor. The author in this paper analyzes the legality of contracting the aforementioned clause in license agreements from the aspect of European Union Competition law, as there are still no positive legal norms governing this institute in domestic law.